2017
DOI: 10.1038/onc.2017.172
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of deubiquitylating enzyme Rpn11 triggers apoptosis in multiple myeloma cells and overcomes bortezomib resistance

Abstract: Proteasome inhibition is an effective therapy for multiple myeloma (MM) patients; however, the emergence of drug resistance is common. Novel therapeutic strategies to overcome proteasome inhibitor resistance are needed. In this study, we examined whether targeting deubiquitylating (DUB) enzymes upstream of 20S proteasome overcomes proteasome inhibitor resistance. Gene expression analysis, immunohistochemical studies of MM patient bone marrow, reverse transcription–PCR and protein analysis show that Rpn11/POH1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 46 publications
(52 reference statements)
3
85
0
Order By: Relevance
“…Research on the efficacy of OPA as a potential cancer treatment has been started in MM. Studies indicate that OPA's metallopeptidase inhibition activity is linked to apoptosis in myeloma cell lines including cell lines, which were BTZ resistant [157].…”
Section: Ra190mentioning
confidence: 99%
“…Research on the efficacy of OPA as a potential cancer treatment has been started in MM. Studies indicate that OPA's metallopeptidase inhibition activity is linked to apoptosis in myeloma cell lines including cell lines, which were BTZ resistant [157].…”
Section: Ra190mentioning
confidence: 99%
“…We and others previously showed that chemical inhibition of Rpn11 blocks cancer cell proliferation (Li et al, 2017; Song et al, 2017). We measured the effects of ETPs on the proliferation of HCT116 human colon cancer cells and calculated inhibition of cell growth (GI 50 ) (Table S2).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, because CZM was discovered as a new drug for cancer treatment 37 , it would be now interesting to investigate whether part of its anti-cancer effects could be the result of inhibiting Golgi-to-ER retrograde pathway. Interestingly, recent studies have shown that PSMD14 is upregulated (mRNA and protein levels) in different tumoral cell types 81, 82 . Whether cancer cells are more dependent of Golgi-to-ER retrograde pathway than normal cells, as it happens regarding the mechanisms of protein quality control 83 is still unclear.…”
Section: Discussionmentioning
confidence: 99%